Future proof: Britain in the 2020s. Issue 4 (March 2017) - Lawrence, Mathew
Abstract : Knowing what the next decade has in store can help progressives to shape the future.Mathew Lawrence outlines the major factors that will impact British lives over the next 10 years – including Brexit, ecological instability, and technological transformations in social and economic life – and argues for a future‐focussed strategy for change.